Resettlement Stories: Photovoice with Adolescent Girls and Young Women with Refugee Backgrounds in Quebec - Bandarchian Rashti, Nesa (Refuge, 2026)
Despite extensive migration research, the resettlement experiences of adolescent girls and young women with refugee backgrounds remain underexplored. This research, grounded in girlhood studies and participatory visual and arts-based methodology, engaged nine participants (ages 14–24) from Haiti, Venezuela, Congo, and Brazil in the province of Quebec, Canada. Through photovoice, participants documented their experiences, highlighting key challenges such as discrimination, mental health struggles, financial insecurity, and educational barriers. While they reported feeling physically safe, systemic barriers continued to hinder their full integration. Findings emphasize the need for targeted support and programs to foster meaningful inclusion and long-term well-being.